Evolution of fast‐growing and more resistant phenotypes in introduced common mullein (Verbascum thapsus). (10th January 2013) - Kumschick, Sabrina; Hufbauer, Ruth A.; Alba, Christina; Blumenthal, Dana M.; Prentice, Honor C.
Summary Species introduced into areas outside of their native range face novel biotic and abiotic conditions, which probably impose novel selection pressures. Adaptation to these new conditions may increase the ability of introduced species to establish and spread. Like many other introduced plant populations, introduced genotypes of common mullein (Verbascum thapsus) are more successful in their introduced than in their native range, with increased growth and fecundity. These differences appear to be at least partly genetically based. The most successful introduced populations also grow in an environment that is drier and has fewer competitors than native populations. It is not known, however, whether differences between native and introduced mullein populations are related to these environmental differences between ranges. We used a common garden experiment with 23 native and 27 introduced populations of common mullein to test whether common mullein in the introduced range exhibits evolutionary shifts with respect to responses to competition, drought stress and nitrogen (N) stress. We also used choice experiments to learn whether introduced mullein is more or less resistant to a generalist herbivore than native mullein. Without competition, introduced genotypes grew larger than native genotypes under high resource availability (control) and N stress, but not water stress. Survival, however, was increased in native populations under competition and N stress. The introduced genotypes also had a lower root:shoot ratio than the native genotypes. With competition, introduced genotypes grew larger than native genotypes across all treatments, with that difference being significant under N stress. The introduced genotypes were also more resistant to a generalist herbivore. Synthesis: Together, high biomass, strong responses to high water availability and low root:shoot ratio suggest that mullein has evolved a fast‐growing, weedy phenotype in its introduced range rather than adapting to a low‐water environment through increased root growth. Although fast‐growing plants can be more palatable to herbivores, in this case there does not appear to be a trade‐off between growth and defence against a generalist herbivore. Mullein appears to have evolved to be both faster growing and better defended in the introduced range.